Pengaruh Penerapan Augmentative Alternative Communication terhadap Kemampuan Bahasa Reseptif pada Anak Cerebral Palsy di Yayasan Pangon Utomo Surakarta - Srilestari, Margareta; Mangunsong, Roy Romey Daulas (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: The use of AAC (augmentative alternative communication) as a communication used for people with cerebral palsy needs to be used habitually in the living environment of people with cerebral palsy. The habituation refers to the behavioristic theory that language development requires a habituation exercise with the use of operant conditioning. Objectives: This study aims to determine the effect of the application of augmentative alternative communication on receptive language skills in children with cerebral palsy at Yayasan Pangon Utomo Surakarta. Methods: This type of research is experimental research with a quantitative approach. This study uses a one group pretest-posttest design where in this study make observations before receiving treatment and compare with the results of observations after receiving treatment. The population in this study were cerebral palsy children and the samples used amounted to 10 cerebral palsy children at the Pangon Utomo Foundation Surakarta. The test used is the Wilcoxon test. Results: The results of the pretest and posttest showed that there was no difference in the decrease obtained from the negative ranks value, but there was an increase of 9 people obtained from the positive ranks value and there was the same value between the pretest and posttest of 1 person. In the Wilcoxon test table, a P value (sig) of 0.006 was obtained, indicating that the P value (Sig) <0.05. Conclusion: There is an effect of the application of augmentative alternative communication on receptive language skills in children with cerebral palsy at the Pangon Utomo Foundation. Keywords : Augmentative Alternative Communication, Receptive Language, Cerebral Palsy